Effect of type 1 diabetes and type 2 diabetes on the risk of venous thromboembolism. Issue 5 (27th November 2020) - Hinton, William; Nemeth, Banne; de Lusignan, Simon; Field, Ben; Feher, Michael D.; Munro, Neil; Roberts, Lara N.; Arya, Roopen; Whyte, Martin B.
Abstract: Aims: Whether diabetes increases venous thromboembolism (VTE) is unclear. Any greater risk may relate to insulin resistance, but many studies did not differentiate between type 1 diabetes and type 2 diabetes for VTE risk. Methods: Retrospective cohort study of the Royal College of General Practitioners Research and Surveillance Centre, comprising over 530 primary care practices. We determined whether type 1 diabetes and/or type 2 diabetes are independent risk factors for VTE. The index date was 1 January 2009, individuals were followed to 31 December 2018, or censoring. Cox proportional hazard regression analysis was used to investigate the risk of VTE in people with type 1 diabetes and type 2 diabetes relative to no diabetes. The primary outcome was occurrence of VTE. The model was adjusted for potential confounders for VTE. Results: There were 7086 people with type 1 diabetes and 95, 566 with type 2 diabetes, diagnosed before 1 January 2009. The non‐diabetes group consisted of 1, 407, 699 people. In the unadjusted analysis, there was no increased risk of VTE with type 1 diabetes (HR 1.00, 95% CI 0.76–1.33) but there was for type 2 diabetes (HR 2.70, 95% CI 2.57–2.84). In the fully adjusted model, VTE risk was increased in type 1 diabetes (HR 1.46, 95% CI 1.11–1.92), but not with type 2 diabetes (HR 1.06, 95% CI 0.98–1.14). Conclusions: Type 1 diabetes was associated with a greater risk for VTE while type 2 diabetes was not. Further work is needed to determine the reason(s) for this.